Fabrication of carbon nanospheres using natural resources and their voltametric studies of dopamine. (2018) - Yallappa, S.; Kiran Kumar, S.R.; Nagashree, K.L.; Uma,; Bhargavi, M.; Rakshitha, C.N.; Aneetta, D.; Abhinethri,; Mrinasha, P.; Hegde, Gurumurthy
Abstract: In this study, mesoporous carbon nanospheres with particle size of ∼ 50 nm and primary mesopores of ∼ 2.0 nm in diameter were prepared and used in the detection of dopamine. The Paper Mulberry bark was employed as the carbon precursor under pyrolysis technique at annealing temperature of 500 °C without adding any catalyst. The formation of carbon nanospheres with high graphitic content is evident from their characteristic X-ray diffraction (XRD). The surface morphology of mesoporous carbon nanospheres were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) and the expected elemental composition by energy dispersive X-ray (EDX) analysis. The electrochemical response of the carbon nanospheres modified carbon paste electrode was found to be 5.0 ×10 −5 M for dopamine at pH 7.2 PBS solution with a scan rate of 50 mVs -1 . Moreover, the modified carbon paste electrode using carbon nanospheres shows an excellent voltammetric response and exhibit excellent electrochemical sensor for dopamine having high sensitivity when compared to the bare carbon paste electrode.